Take A Walk With TESCO - New Straits Times, Noel Achariam (2008)
Make a difference this July 27 by joining the Tesco Malaysia Walk For Life 2008 event at Taman Tasik Titiwangsa and help raise funds for research into the prevention and treatment of cancer.